Solution-Focused Brief Therapy Group Counseling to Increase Academic Resilience and Self-Efficacy - Hendar, Kus; Awalya, Awalya; Sunawan, Sunawan (Jurnal Bimbingan Konseling, 2020)
The purpose of this study was to examine and analyze the effectiveness of Solution Focused Brief Therapy group counseling to increase academic resilience and self-efficacy. This study used a pre-test – post-test control group design. The purposive sampling technique was used to select 14 students as experimental subjects who placed randomly into two groups so that each group consisted of seven students. The MANOVA test results showed that Solution Focused Brief Therapy counseling group was effective in increasing academic resilience (F(3.10) = 36.40; ηp2 = 0.91; p < 0.01) and self-efficacy (F(3.10) = 40.62; ηp2 = 0.92; p < 0.01). Furthermore, the Wilcoxon test results showed that in the experimental group there was an enhancement in academic resilience (Z = -2.38; p < 0.05) and self-efficacy (Z = -2.41; p < 0.05). The control group showed an enhancement in academic resilience (Z = -2.53; p < 0.05) but self-efficacy showed there was not enhancement (Z = -1.85; p > 0.05). The findings of this study conveyed that the Solution Focused Brief Therapy counseling group was effective in increasing academic resilience and self-efficacy.